Does Audit Firm Size and Audit Tenure Influence Fraudulent Financial Statements? - Elly Suryani; Srihadi Winarningsi; Ilya Avianti; Poppy Sofia; Nanny Dewi (Australasian Accounting, Business and Finance Journal, 2023)
The phenomenon of financial statement fraud in Indonesia often occurs, related to reports on audit results of public accounting firms. These findings have an impact on investors because of fraudulent financial statements that have the potential to cause losses. The purpose of the study was to determine the effect of the size and tenure of KAP on the detection of financial statement fraud. The research sample was 140 manufacturing companies from 2014 to 2015, which were listed on the Indonesia Stock Exchange using a purposive sampling technique. Data analysis research used SPSS version 20. Descriptive analysis used multiple regression. This research finds that the size of the audit firm and the tenure of the audit did not significantly affect the indications of fraudulent financial statements as measured by the Sales Growth Index (SGI), Gross Margin Index (GMI), Asset Quality Index (AQI), Days' Sales Receivable Index (DSRI) indicators, Sales, General and Administrative Expenses Index (SGAI), Leverage Index (LVGI), Total Accrual to Total Assets (TATA) and Messod D Beneish-Score (M-Score), but have a significant effect on fraudulent financial indication reports as measured by the Depreciation Index indicator (DEPI).
Keywords: Audit Firm Size; Audit Tenure; Fraudulent Financial Statements